Implementasi Rehabilitasi Medis dan Sosial Terhadap Narapidana Narkotika Pada Lembaga Pemasyarakatan - Zainab Ompu Jainah; Yoga Dwi Anggara (Legitimasi: Jurnal Hukum Pidana dan Politik Hukum, 2022)
One of the development activities for inmates is the provision of medical rehabilitation and social rehabilitation for drug offenders. Implementation of medical and social rehabilitation for drug offenders at Class II B Gunung Sugih Prison in accordance with Director General of Prisons Order No. PAS-36.OT.02.02 of 2020 about Correctional Service Standards is the focus of this research. This study examines the adoption of medical and social rehabilitation programs for drug offenders. What obstacles impede the implementation of medical and social rehabilitation programs for drug offenders? This study employs a normative and empirical legal methodology. The findings indicate: The execution of medical and social rehabilitation for drug convicts begins with an assessment of the client's concerns so that medical and social rehabilitation can be applied promptly. Acceptance occurs after determining the nature of the client's problem, as well as his or her physical, psychological, social psychological, and level of expertise, while simultaneously assigning the client to several sorts of programs. The purpose of social and skill mentoring is to improve client interaction patterns, preserve emotional stability, build a sense of responsibility and discipline, and foster the desire to become a better individual. Insufficient medical equipment and infrastructure of buildings and special rooms prevent medical and social rehabilitation from taking place. There are drug users in prison who suffer from serious diseases and a lack of family support.